EVALUATION OF AWARENESS AND KNOWLEDGE OF IONIZING RADIATION-RELATED HAZARDS AND PROTECTIVE MEASURES AMONG PATIENT’S ACCOMPANYING PERSONS/CARETAKER IN BUNDELKHAND REGION OF CENTRAL INDIA IN A TERTIARY LEVEL TEACHING HOSPITAL IN BUNDELKH AND A MEDICAL COLLEGE, SAGAR (MADHYA PRADESH) - Singh, Punya Pratap; AHIRWAR, VRESHBHAN; NAAGAR, JAGRATI KIRAN; SAHU, MANOJ; RAJESH KUMAR MAURYA,; PRABHAT VERMA, (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Evaluation of awareness and knowledge of ionizing radiation related hazards and protective measures among patient’s accompanying persons or caretaker in Bundelkhand region of central India in a tertiary level teaching hospital in Bundelkhand Medical College, Sagar, (M.P.). Methods: This study was conducted as a questionnaire-based survey conducted in one tertiary-level teaching hospital in Bundelkhand Medical College, Sagar, M.P., from June 2021 to February 2022. A semi-structured questionnaire of 21 items was administered to 840 patient’s accompanying persons/caretaker selected as per inclusion/exclusion criteria. Information on demographic variables of the respondents intheir knowledge about ionizing radiation effects/hazard, radiation protection measures and source of their knowledge on ionizing radiation were taken and collected data used in the study by applying descriptive statistical analysis. Results: Majority of the participants in our study were male 548 (63.3%). Most of the participants, 635 (75.6%), did not have knowledge of ionizing radiation. Only 320 (38%) knew that ionizing radiation is hazardous. The majority of the participants, 399 (76.7%), were informed about radiation by the radiographers, while 121 (23.2%) read about it. A larger number of the participants, 620 (73.8%), had no idea about the meaning of radiation protection. The majority of the participants, 678 (80.2%), assisted their relatives during the examination. Most of the participants, 676 (80.1%), have seen the radiation warning sign before. Conclusion: This study showed that there is a low level of knowledge and awareness of radiation hazards and protective measures among patients’ accompanying persons or caretakers. It is obvious that public education via new papers, TV, holdings, etc. will contribute immensely to the spreading of awareness of the harmful effects of ionizing radiation and the measurement of for radiation protection measures.